A proposed model of the development of suicidal ideations - Gvion, Yari; Horesh, Netta; Levi-Belz, Yossi; Apter, Alan (Comprehensive psychiatry, 2015)
Suicidal ideations may precede suicide attempts. They are of particular concern in psychiatric populations because psychopathology is a major risk factor for suicide. The factors affecting the development of suicide ideations may differ among psychiatric patients with and without a previous suicide attempt and individuals without a psychiatric diagnosis. The aim of this study is to develop a model of suicide ideation in psychiatric patients and the general population. The study included 196 participants: 92 psychiatric patients with a previous suicide attempt (“attempters”); 47 psychiatric patients who had never attempted suicide (“non-attempters”); and 57 healthy control subjects. Data were collected on socio-demographic parameters, clinical history, and details of the suicide attempts. Participants completed a battery of psychological instruments assessing aggression–impulsivity, mental pain (including depression and hopelessness) and communication difficulties, in addition to negative life events. Findings were correlated with suicidal ideation by group. The correlations of the different variables with suicidal ideation differed between suicide attempters and non-attempters; therefore, the model was analyzed separately for each group. The study yielded three major findings: negative life events had a significant effect on both anger-in and impulsivity in non-attempters but not in attempters; hopelessness moderately contributed to suicidal ideations in attempters but not in non-attempters; loneliness contributed significantly to depression in non-attempters but was less distressing in attempters. The mechanism underlying suicidal ideation appears to differ between psychiatric patients who have previously attempted suicide and those who have not, supporting a dual model of suicidal ideation. Although this is only a preliminary study, these findings are important for furthering our understanding of the process of transition of suicidal thoughts to completion of suicide. These results need further replication with a larger cohort of subjects.